ERROR ANALYSIS OF THE USE JAPANESE VERB MEANINGFUL ‘WEAR’ IN JAPANESE STUDENT OF JAPANESE LANGUAGE DEPARTMENT FACULTY OF LANGUAGE WIDYATAMA UNIVERSITY (International Journal of Psychosocial Rehabilitation, 2020)
Language errors generally occur due to differences in language structure, number of meanings in a word, and the meaning of the word is often different based on conditions and situations. The error that appears can be an error using vocabulary or the use of sentences pattern. This research is focused on the error analysis of verb use in Japanese that is done by students of semester IV and semester VI of Japanese Language Department Faculty of Language University Widyatama. The purpose of this research is to know which verbs often mistake in its use, comparing among students of the semester IV and VI which often make mistakes of use and what factors caused the error. The method used in this research is a descriptive method. The instruments used to obtain data are test instruments and polls. Data collection technique is one shoot model, that is by taking data done once at one time. The sample in this study was the semester students of IV and VI Japanese Language Department Faculty of Language Widyatama University. Based on the results of the research known that the mistake of use is more done by students of semester VI especially on the verb shimeru with 71% error, hameru with 58% error, and maku with 58% error, while the mistake of use in students of semester IV is the verb hameru as much as 50% error, shimeru as much as 50% error, and haku as much as 37% eror. The cause of the mistake of using verbs is the number of Japanese verbs that mean ' to wear ' with varying meanings in one type of verb. In addition, the verb uses are not specifically studied in the basic level Japanese language module, so the lack of understanding and learning experience becomes one factor of the occurrence of mistakes.